2020
DOI: 10.1002/hyp.13843
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐annual variability in snow cover depletion patterns and atmospheric circulation indices in the Upper Irtysh basin, Central Asia

Abstract: The Irtysh River is the main water resource of Eastern Kazakhstan and its upper basin is severely affected by spring floods each year, primarily as a result of snowmelt. Knowledge of the large‐scale processes that influence the timing of these snow‐induced floods is currently lacking, but critical for the management of water resources in the area. In this study, we evaluated the variability in winter–spring snow cover in five major sub‐basins of the Upper Irtysh basin between 2000 and 2017 as a possible explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…These activities are, in fact, dependent on the snow depth and distribution, and they are severely affected by the current climate change, which can lead to a reduction in snow cover as the increasing air temperature leads to more precipitation falling as rain and earlier snowmelt in the spring [14]. Moreover, snow may cause natural disasters such as avalanches or floods as a consequence of the melting process [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These activities are, in fact, dependent on the snow depth and distribution, and they are severely affected by the current climate change, which can lead to a reduction in snow cover as the increasing air temperature leads to more precipitation falling as rain and earlier snowmelt in the spring [14]. Moreover, snow may cause natural disasters such as avalanches or floods as a consequence of the melting process [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to AVHRR, MODIS benefits from a finer spatial resolution (500 m) and the availability of validated snow cover products such as MOD10A1 [25], and although it has a shorter period of data coverage (since 2000), it has now reached 20 years in orbit, building an invaluable data record and approaching the minimum time required for climatological analysis. Several studies have employed MODIS, based on either the daily or the 8-day product, to investigate the spatial distribution and interannual variability in snow cover at the regional scale and to estimate the runoff characteristics [16,26,27]. Some studies have also included the Alps as part of a larger area: for instance, Dietz et al [28] observed snow cover characteristics in Europe from 2000 to 2011, while Notarnicola et al [29] investigated snow cover changes over major mountain chains of the planet from 2000 to 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite images permitted the description of glacier albedo [48][49][50], which is diminishing in the Alps [51] due to increasing debris and black carbon deposition. Furthermore, remote sensing highly improved snow cover mapping, thus permitting researchers to describe snow depletion and to compute more accurately the water budget of a mountain catchment [52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%